Urban Floods, Clientelism, and the Political Ecology of the State in Latin America. Issue 5 (2nd September 2020) - Coates, Robert; Nygren, Anja
Abstract : In this article, we examine the coproduction of hazardous urban space and new formations of clientelist state governance. Work on hazards and vulnerability frequently demonstrates how hazardous urban spaces are produced, but a critical understanding of state power is often left untouched. Correspondingly, scholars analyzing clientelism and state formation habitually discuss the configuration of new forms of governance and the consolidation of state power without intersecting these processes with the production of vulnerabilities and "hazardous nature." Drawing on ethnographic research in urban areas susceptible to serious floods and landslides in Brazil and Mexico, we argue that clientelist governance and state making, including complex forms of political favoritism, create urban hazardscapes, as much as the management of urban disasters acts to reconfigure patron–client relations within "hazardstates." The article contributes to an emerging body of literature analyzing linkages between urban environmental governance, state authority, and the reproduction of vulnerability.